2015
DOI: 10.1089/lap.2014.0485
|View full text |Cite
|
Sign up to set email alerts
|

The Guidance Impact of Preoperative Magnetic Resonance Cholangiopancreatography on Laparoscopic Cholecystectomy

Abstract: Our results demonstrated that preoperative MRCP had a robust safeguarding effect on LC and deserves further promotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…MRCP is a noninvasive imaging modality which can optimally image the bile ducts and cystic duct. Studies have shown that preoperative MRCP provides important information regarding cystic duct anatomy and has a significant safeguarding effect on laparoscopic cholecystectomy [ 6 8 ]. Prior knowledge of the cystic duct anatomy and its variants helps in proper interpretation of disease process and avoids iatrogenic injuries.…”
Section: Discussionmentioning
confidence: 99%
“…MRCP is a noninvasive imaging modality which can optimally image the bile ducts and cystic duct. Studies have shown that preoperative MRCP provides important information regarding cystic duct anatomy and has a significant safeguarding effect on laparoscopic cholecystectomy [ 6 8 ]. Prior knowledge of the cystic duct anatomy and its variants helps in proper interpretation of disease process and avoids iatrogenic injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Under this notion and taking into account additionally the great anatomical variability of the extrahepatic biliary tree, it becomes evident that accurate pre-operative planning could play a crucial role in performing a safe cholecystectomy, particularly for the majority of general surgeons who do not have specialist hepatobiliary experience [ 2 , 3 ]. As a result, the liberal use of pre-operative magnetic resonance cholangiopancreatography (MRCP) is gaining popularity as a roadmap prior to cholecystectomy, aiming to assess primarily for the presence of migrated gallstones within the cystic duct or common bile duct, as well as providing information regarding the anatomical features of the extrahepatic biliary tree on an individualised basis [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MRCP is a noninvasive imaging technique for optimally visualizing the cystic duct and bile ducts. According to studies, MRCP offers essential information on the structure of the cystic duct pre-operatively and has a significant protective role on laparoscopic cholecystectomy[15][16][17]. Prior knowledge of the cystic duct's anatomy and its variations benefits in the appropriate understanding of the disease process and…”
mentioning
confidence: 99%